Metode Bimbingan Islami dalam Membentuk Akhlak Anak - Muhibbah Muhibbah; Mawardi Siregar; Sabrida M. Ilyas (Prodi Bimbingan dan Konseling Islam, 2020)
The purpose of this study are 1) To find out the Islamic guidance method in shaping children's morals at the Al-Hakim Paya Kulbi orphanage in Aceh Tamiang District, 2) to find out the implications of Islamic guidance in shaping children's morals at the Al-Hakim Paya Kulbi in Aceh Tamiang District. This type of research is field research. This is a qualitative descriptive study conducted directly on the object under study to obtain the data needed, meaning that the individual researchers talk and directly observe the people being examined using the method of observation, interviews, and documentation. As the findings of the data obtained by researchers from primary data sources, namely orphanage children and administrators/educators of the orphanage. The results showed that the Islamic guidance method in shaping the character of children in the al-Hakim Paya Kulbi orphanage in Aceh Tamiang Regency is by using; 1) exemplary methods; 2) habituation methods; and 3) lecture methods. Furthermore, the implications of Islamic guidance in shaping the morals of children in the al-Hakim Paya Kulbi orphanage in Aceh Tamiang Regency are the formation of good behavior in the orphans, increased religious practices (praying, reciting in daily life, increasing the craft of orphans, and the formation of independence in the orphanage self orphanage.